IPTEKS DAN STRATEGI PENGEMBANGANNYA - Widisuseno, Iriyanto (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper discusses the development of science and technology in Indonesia based on Pancasila values​​. The role Pancasila as paradigm of the development of science to gain awareness, that science and technology are not value-free. It is therefore recognized that the development of science and technology cannot be separated from ethical considerations, religious, and cultural values ​​which are aimed at establishing a civilized human life. Keywords: Pancasila, science, strategy, technology